EFEKTIVITAS PROGRAM KELOMPOK USAHA BERSAMA DI DESA KAMANGA DUA KECAMATAN TOMPASO KABUPATEN MINAHASA - MOMONGAN, BRENDA ANGGRELLA; LALOMA, ALDEN; TAMPI, GUSTAAF BUDI (JURNAL ADMINISTRASI PUBLIK, 2018)
Poverty cannot be separated from the context of community development. Communitydevelopment means as a conscious, systematic and directed effort organized by, for and in society thataims to change their own standard of living in a better direction. Therefore, many things are done indealing with poverty, both from the government, the private sector and from the public. One of theprograms carried out by the government in handling poverty is through the Joint Business Group(KUBE). The community can utilize and participate in the Joint Business Group (KUBE) which isadjusted to expertise supported by environmental conditions that are carried out in groups to deal with theproblems of poverty that have taken root in a community. The Joint Business Group in Kamanga DuaVillage is largely targeted by the community in accordance with the criteria set by the government, namelythe people belonging to the weak economy are also adjusted to their environmental conditions andcapabilities. The purpose of this study was to determine the effectiveness of the Joint Business GroupProgram in Kamanga Dua Village, Tompaso District, Minahasa District. This study uses a qualitativemethod. The informants in this study were seven people. Data collection techniques used were interviews,observation and documentation. Measurements using the theory from Ducan quoted by Richard M. Seterswith three points of measure of effectiveness, namely achievement of goals, integration, adaptation. Theresults of this study state that by using three points of measurement of the effectiveness of the KUBEprogram in Kamanga Dua Village, Tompaso Subdistrict, Minahasa Regency is considered to have runwell. Suggestions further enhance the ability of members and groups and improve infrastructure facilities.